2019
DOI: 10.1039/c8nr08498j
|View full text |Cite
|
Sign up to set email alerts
|

Explosible nanocapsules excited by pulsed microwaves for efficient thermoacoustic-chemo combination therapy

Abstract: Microwave irradiation is a powerful non-invasive approach for treating deep-seated diseases in a clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…It was reported that after pulsed microwave irradiation, the nanocapsules absorbed energy to generate a large thermoacoustic shockwave that simultaneously decomposed molecules into carbon dioxide and ammonia, causing cavitation and, consequently, cellular damage. The thermoacoustic shockwave and the gas burst also mechanically disrupted intracellular organelles, which resulted in a high ratio of necrotic cells, and DOX was released from the cytosol into the nucleus to initiate cell death [308].…”
Section: Iontophoresismentioning
confidence: 99%
“…It was reported that after pulsed microwave irradiation, the nanocapsules absorbed energy to generate a large thermoacoustic shockwave that simultaneously decomposed molecules into carbon dioxide and ammonia, causing cavitation and, consequently, cellular damage. The thermoacoustic shockwave and the gas burst also mechanically disrupted intracellular organelles, which resulted in a high ratio of necrotic cells, and DOX was released from the cytosol into the nucleus to initiate cell death [308].…”
Section: Iontophoresismentioning
confidence: 99%
“…This confined heat results in thermoelastic expansion and then produces shockwaves via thermal acoustic cavitation. [ 30–33,48,49 ]…”
Section: Introductionmentioning
confidence: 99%
“…More than 300 natural amino acids have been found, but only 20 amino acids take part in the human protein synthesis ( Canfield and Bradshaw, 2019 ; Kelly and Pearce, 2020 ). Most of the 20 amino acids are good raw materials for fabricating micelles, for example, lysine ( Itaka et al, 2003 ; Cheng et al, 2021 ; Kanto et al, 2021 ), arginine ( Yao et al, 2016 ; Jiao et al, 2019 ), histidine ( Guan et al, 2019 ; Wang Z. et al, 2019 ), glutamic acid ( Krivitsky et al, 2018 ; Ma et al, 2020 ; Brunato et al, 2021 ), aspartic acid ( Yeh et al, 2013 ; Teng et al, 2017 ), cysteine ( Xu W. et al, 2015 ). Among them, there are three basic amino acids namely, lysine, histidine, and arginine, whose side chains contain amino, imidazolyl, and guanidine groups, respectively.…”
Section: Introductionmentioning
confidence: 99%